PENGARUH PROFESIONALISASI GURU DAN SUPERVISI KEPALA SEKOLAH TERHADAP ETOS KERJA GURU SMP NEGERI SE KECAMATAN TULUNG SELAPAN - Anggun Pratiwi (Jurnal Manajemen Pendidikan, 2026)
Objective:Educational quality is strongly influenced by teachers’ performance in the learning process. Teacher perfomence is affected by several factors, particularly teacher professionalization and principal supervision. This study aims to examine the effects of teacher professionalization and principal supervision on the work ethic of public junior high school teachers in Tulung Selapan Subdistrict.This study employed a quantitative approach using a survey method. Data were collected through questionnaires and analyzed using descriptive statistics and regression analysis. The results indicate that teacher professionalization and principal supervision have significant effects, both partially and simultaneously, on teachers’ work ethic. These findings suggest that improving teachers’ work ethic can be achieved through strengthening professional competence and implementing effective principal supervision